2018
DOI: 10.3389/feart.2018.00215
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Noble Gases and CO2 in Fluid Inclusions From Lithospheric Mantle Beneath Wilcza Góra (Lower Silesia, Southwest Poland)

Abstract: Knowledge of the products originating from the subcontinental lithospheric mantle (SCLM) is crucial for constraining the geochemical features and evolution of the mantle. This study investigated the chemistry and isotope composition (noble gases and CO 2 ) of fluid inclusions (FI) from selected mantle xenoliths originating from Wilcza Góra (Lower Silesia, southwest Poland), with the aim of integrating their petrography and mineral chemistry. Mantle xenoliths are mostly harzburgites and sometimes bear amphibole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 96 publications
1
40
0
Order By: Relevance
“…We highlight that the addition of secondary He occurs in the crystal matrix as observed in FI study. In addition, reticular helium is normally released via rock/mineral melting or multistep crushing, while we used single‐step crushing, which is a conservative method in order to minimize the release of helium from the crystal matrix (e.g., Correale et al, ; Kurz, ; Rizzo et al, ). However, other studies that used our approach found that in a sufficient time span a certain percentage of helium might diffuse from the crystal matrix into the FIs (Barry et al, ; Day et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We highlight that the addition of secondary He occurs in the crystal matrix as observed in FI study. In addition, reticular helium is normally released via rock/mineral melting or multistep crushing, while we used single‐step crushing, which is a conservative method in order to minimize the release of helium from the crystal matrix (e.g., Correale et al, ; Kurz, ; Rizzo et al, ). However, other studies that used our approach found that in a sufficient time span a certain percentage of helium might diffuse from the crystal matrix into the FIs (Barry et al, ; Day et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The analytical uncertainty (1 σ ) of the He isotopic ratio is between 1.5% and 15% and that of 20 Ne is <0.4%. 20 Ne was corrected for isobaric interference at m / z 20 ( 40 Ar 2+ ) in accordance with INGV‐Palermo analytical protocol (e.g., Rizzo et al, ). 40 Ar was analyzed by a multicollector mass spectrometer (GVI Argus), with an analytical uncertainty (1 σ ) generally <0.4%.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 3 more Smart Citations